2015
DOI: 10.1096/fj.15-272450
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP protects against sepsis through macrophage P2X7 purinergic receptors by enhancing intracellular bacterial killing

Abstract: Extracellular ATP binds to and signals through P2X7 receptors (P2X7Rs) to modulate immune function in both inflammasome-dependent and -independent manners. In this study, P2X72/2 mice, the pharmacological agonists ATP-magnesium salt (Mg-ATP; 100 mg/kg, EC 50 1.32 mM) and benzoylbenzoyl-ATP (Bz-ATP; 10 mg/kg, EC 50 285 mM), and antagonist oxidized ATP (oxi-ATP; 40 mg/kg, IC 50 100 mM) were used to show that P2X7R activation is crucial for the control of mortality, bacterial dissemination, and inflammation in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 49 publications
7
94
1
Order By: Relevance
“…Moreover, inhibition of P2X7 by a selective antagonist suppressed the NLRP3/ASC/caspase-1 signaling cascade and IL-1␤ release, arresting further lung injury (57). It has been shown that P2X7 also plays a role in the regulation of the immune system, such as in protecting against sepsis (7). Signaling through P2X7 on macrophages was found to reduce sepsis proliferation and provide antibacterial effects (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inhibition of P2X7 by a selective antagonist suppressed the NLRP3/ASC/caspase-1 signaling cascade and IL-1␤ release, arresting further lung injury (57). It has been shown that P2X7 also plays a role in the regulation of the immune system, such as in protecting against sepsis (7). Signaling through P2X7 on macrophages was found to reduce sepsis proliferation and provide antibacterial effects (7).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that P2X7 also plays a role in the regulation of the immune system, such as in protecting against sepsis (7). Signaling through P2X7 on macrophages was found to reduce sepsis proliferation and provide antibacterial effects (7). A study using P2X7 KO mice demonstrated that the receptor is required for development of the inflammatory response associated with sepsis (50).…”
Section: Discussionmentioning
confidence: 99%
“…Xiang et al showed that ATP offered protection from peritonitis in mice infected with Staphylococcus aureus and Escherichia coli [12]. Csoka et al demonstrated the ability of macrophages to increase intracellular killing of E. coli through purinergic receptors during sepsis, highlighting the beneficial effects of ATP through the inflammasome in an in vivo model [19]. …”
Section: Introductionmentioning
confidence: 99%
“…TNF-α, IL-1β, and NO release in LPS-primed macrophages is blocked by POM-1 eATP, acting via P2X7R, induces production and release of IL-1β by activation of the NLRP3/caspase-1 complex [13]. We examined the effects of POM-1 on IL-1β and TNF-α secretion by LPS-primed macrophages in response to 3 mM ATP.…”
Section: Bleb Formation In Response To Atp Is Not Blocked By Pom-1mentioning
confidence: 99%
“…P2X7R activation has been widely studied as a trigger of the NLRP3 inflammasome, but eATP through P2X7R can modulate immune functions even in an inflammasomeindependent manner [13]. P2X7R can induce cell death, cytokine release, killing of intracellular pathogens, and membrane blebbing [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%